AN ANALYSIS OF ROAD SIGN TERMS FORMED BY COMPOSITIONAL METHOD - Khushbakova Nasiba Nurkobil kizi (Western European Studies, 2025)
Road signs are a critical communicative interface in modern transportation, demanding rapid and unambiguous information conveyance. This paper presents a linguistic analysis of English road sign terms formed through compositional methods, where multiple lexical units combine to create single, distinct semantic entities. The study investigates the systematic construction and interpretation of these multi-word expressions, aiming to illuminate the linguistic principles underpinning the creation of effective, concise, and universally understandable directives and warnings. Drawing on theories of word formation, particularly compounding as defined by scholars like V.V. Vinogradov, the analysis explores the morpho-syntactic patterns and semantic functions inherent in these specialized terms. The paper identifies prevalent grammatical structures in compositional road sign terms, including Adjective + Noun (e.g., "Two-way traffic"), Noun + Noun (e.g., "Road work"), "No" + Noun/Gerund (e.g., "No entry"), Verb + Noun/Adverb (e.g., "Turn left"), and more complex multi-word constructions. By examining these patterns, the study contributes to a broader understanding of specialized terminologies and the linguistic strategies employed in highstakes, time-sensitive communication within the vital domain of traffic management and public safety
Keywords: Road Signs; Compositional Method; Linguistic Analysis